Child Education in the Qur'anic Perspective: Tafsir Tarbawi Analysis and Its Implications for Modern Education - Alfani, Ilzam Hubby Dzikrillah; Mukhsin, Mukhsin; Khusnadin, Muhammad Hafidz; Addzaky, Khoirul Umam; Mawaddah, Putri Wanda (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
As technology advances, children’s character development is shaped by their experiences. Therefore, it is the responsibility of parents to provide continuous guidance to help children differentiate between right and wrong. This study explores the educational strategies of Luqman and their relevance to modern education. Using a qualitative approach, this research employs an analytical description based on relevant references. The study identifies five key principles for effective education: meeting the child’s needs, learning through play, creating a conducive learning environment, implementing gradual learning, and reinforcing learning through repetition. Surah Luqman [31]: 12-18 emphasizes four core values in early childhood education: Tawhid (belief in the oneness of Allah), noble character, balanced education (both worldly and spiritual knowledge), and role modeling through dialogue. These values align with modern education, which advocates an integrated approach that combines spiritual, cognitive, affective, and psychomotor aspects. Education should not only develop knowledge but also foster wisdom, emotional intelligence, and ethical behavior. To ensure holistic character development, comprehensive evaluation methods are necessary to balance intellectual and spiritual growth.